SURVEY OF THE STATUS OF THE MEDICINAL PLANT TRADE IN DURBAN, SOUTH AFRICA. - Naidoo, Kuben; Coopoosamy, Roger; Singh, Karishma (Student's Journal of Health Research Africa, 2024)
Background This study aimed to identify important plants and parts of medicinally harvested species traded in the Durban medicinal (muthi) market. A better understanding of the extent of the medicinal plant trade is necessary to enable conservationists and municipal managers to better manage threatened species and to take preventative action to protect this valuable resource. Methods Thirty traditional healers from the Durban muthi market in KwaZulu-Natal were interviewed and information was gathered on important plants and parts that were traded. Information was compared to previous data to ascertain whether muthi plants were being exploited. Results Approximately 13 species were widely harvested and sold at the Durban muthi market which includes: Siphonochilus aethiopicus, Hypoxis gerrardii, Aloe aristate, Scilla natalensis, Eucomis autumalis, Senecio serratuloides, Warburgia salutaris, Chrysanthemoides monilifera., Artemisia afra, Bidens Pilosa, Aloe ferox, Haworthia limifolia, Ocotea bullata. These species are sold to cure a wide variety of ailments. The most common plant parts that are traded are the leaves and the stems although other parts are also collected. Single species are preferred rather than a mixture of parts from different plants. Approximately 22% of individuals interviewed indicated that they practiced unsustainable harvesting mainly due to poor harvesting practices and a lack of knowledge of the threatened status of many important species. Conclusion Domestication and mass cultivation may be key strategies to redress exploitation and unsustainable harvesting practices. Recommendation To address these issues, a multifaceted approach is required, including community engagement, improved regulatory enforcement, and initiatives to promote sustainable harvesting and cultivation practices.